Secure Data transmission using Recombinant DNA Cryptography and Morse Code Pattern - G, Santhi (International Journal of Computer Sciences and Engineering, 2020)
It is most important for an organization and individuals to secure their information from attackers and hackers to ensure information privacy, integrity and confidentiality of the data. To enhance the data security across the network, it is very significant to encode the data in unreadable form. Many research works are carried out in the evolution of cryptographic system however current development in this field is DNA Cryptography which is developed based on the computational ability of Deoxyribo Nucleic Acid (DNA). This paper provides triple layer security for data transmission in two methods. In first method, the encryption of the plain text into tRNA by Transcription method. Secondly, the generation of Morse code Pattern which improves the security of the message. In this method the tRNA is generated by DNA code and complementary rule.